Nutritional Values and Health Protective Properties Of Coconut Oil (Indonesian Journal of Pharmaceutical and Clinical Research, 2020)
Chemically, fat or oil is a mixture of triacylglycerol molecules, in which glycerol esterified with three fatty acids. Fatty acid is a monocarboxilic acid containing even number of carbon atom started from 4 to 22. Based on the length of fatty acid in triacylglycerol, fats and oils can be classified into two groups; medium chain triglycerides and long chain triglycerides. Coconut oil belongs to medium chain triglycerides oil because it’s fatty acids consist mostly of medium chain fatty acids (C4:0 to C12:0) and dominated by lauric acid (C12:0), hence usually called as lauric oil. In the year of 1950s, coconut oil was claimed that saturated fats, including coconut oil, could increase blood total cholesterol and hence is atherogenic, while unsaturated fats decrease total cholesterol. However, in 1990s, coconut oil was found to be different from the other saturated oils. Coconut oil composed of medium chain fatty acids with high amount of lauric acid. Coconut oil is metabolized differently from long chain triglycerides saturated oil, and therefore coconut oil has numerous beneficial nutritional values and health promotion. Consumption of food rich in medium chain fatty acids reduces the level of body fat and the decrease the risk of heart disease, diabetes, increase mother’s milk quality and active as potential antibacterial agent.